2022
DOI: 10.1111/1365-2435.14092
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism dramatically alters the ecosystem services provided by freshwater mussels

Abstract: 1. Parasites can indirectly affect ecosystem function by altering host phenotype, but the trait-mediated impacts of parasitism at an ecosystem level remain poorly characterised. However, understanding the influence of parasites is central to understanding the ecosystem services provided by host species, especially in an era of global environmental change.2. We examined the effect of native (the trematode Rhipidocotyle campanula) and invasive (the bitterling fish Rhodeus amarus) parasites, and their interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 89 publications
0
7
0
Order By: Relevance
“…Furthermore, population genetic structure can also affect infection rates through differences in defences between individuals, which could affect observed co‐occurrences in structured fashion (Sallinen et al, 2020 ). Competition is therefore not the only explanation for the negative co‐occurrences of parasite species, though recent experimental evidence from this system shows the presence of one parasite can inhibit the infection of another (Brian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, population genetic structure can also affect infection rates through differences in defences between individuals, which could affect observed co‐occurrences in structured fashion (Sallinen et al, 2020 ). Competition is therefore not the only explanation for the negative co‐occurrences of parasite species, though recent experimental evidence from this system shows the presence of one parasite can inhibit the infection of another (Brian et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Because mites can damage gill tissue (e.g., Fisher et al., 2000 ; Walker, 2017 ), which mussels use to filter water, parasites could also reduce the ecosystem services provided. Further, parasites significantly affect the filtration services provided by mussels, an effect that scales to the ecosystem level (Brian et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hematophages were placed under the pathogen group, as animals with these feeding habitats can be disease vectors (Blitzer et al, 2012). Similarly, we placed parasites and parasitoids under the pathogen group, as Brian et al (2022) demonstrated that parasites can alter wider ecosystem processes by changing the phenotype of their host and should thus be integrated into ecosystem process analyses.…”
Section: Methodsmentioning
confidence: 99%